Port turnaround time: the problems and recommendations / Hairul Anuar - Anuar, Hairul (1995)
Port turnaround time can be classified as turnaround time of vessel and turnaround time of cargo. Turnaround time of vessel is the time where the vessels spend at the wharf and turnaround time of cargo is the time taken to discharge or load the cargo. Fast turnaround time will minimise port stay and give good image for the port and it is alsqwill be economical for the shipping lines. This study will try to identify the problems faced by the port management, shipping agents, forwarding agents and hauilers that involved in the container ship's operations that effect the turnaround time of vessel at Johor Port Container Terminal, Pasir Gudang, Johor. Through the analysis done, a few recommendations had been proposed in order to overcome the problems faced by the port and other parties involved